2002
DOI: 10.1179/003258902225007069
|View full text |Cite
|
Sign up to set email alerts
|

Friction measurement in powder die compaction by shear plate technique

Abstract: The paper explores the use of a shear plate technique paction process and this includes both compression and to measure the frictional characteristics between a ejection. compacted powder and a target surface. The study A number of investigations have been reported in the con rms that the shear plate technique is valid to literature that focus on friction measurement. Essentially measure these frictional characteristics and that any most of the tests described in the literature can be grouped variability in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 0 publications
1
16
0
Order By: Relevance
“…From the presented results it can be observed that the friction coefficient decreases with an increase of normal stress or density of the powder compact, and a steep increase in friction coefficient is observed with increase of sliding velocity from 0 to roughly 30 mm/s, after which point it becomes relatively steady. Similar trends were observed in other studies [10,13,24,25,33,51,66,80,89,90,109,110,111,114,[124][125][126] Further, the influence of temperature on friction coefficient was studied. For this the slab was fitted with thermal resistors and several tests were conducted between 20 and 80°C to assimilate manufacturing conditions, where due friction and high production rate, temperature of the tools and the ejected green compact may reach close to 70°C [19,21,27,86].…”
Section: Friction Measurement Using Shear-plate Devicesupporting
confidence: 84%
See 1 more Smart Citation
“…From the presented results it can be observed that the friction coefficient decreases with an increase of normal stress or density of the powder compact, and a steep increase in friction coefficient is observed with increase of sliding velocity from 0 to roughly 30 mm/s, after which point it becomes relatively steady. Similar trends were observed in other studies [10,13,24,25,33,51,66,80,89,90,109,110,111,114,[124][125][126] Further, the influence of temperature on friction coefficient was studied. For this the slab was fitted with thermal resistors and several tests were conducted between 20 and 80°C to assimilate manufacturing conditions, where due friction and high production rate, temperature of the tools and the ejected green compact may reach close to 70°C [19,21,27,86].…”
Section: Friction Measurement Using Shear-plate Devicesupporting
confidence: 84%
“…Thus, knowing frictional behaviour at powder-tool interfaces is essential for controlling these limiting factors. At present there are a number of friction measuring devices among which the most commonly used are the instrumented-die and the shear-plate device [10,13,19,21,31,45,86,89].…”
Section: Friction In Powder Compactionmentioning
confidence: 99%
“…Consequently, the volumetric strain increment is expressed as [106] dε v = dε 1 + dε 2 + dε 3 = − dρ ρ = dλ 2 9 β 2 σ m (12) Further, the plastic work, dW, done per unit volume of powder (or porous) body may be expressed as a function of yield stress, σ , and effective strain increments, dε , as [106] dW = σ 1 dε 1 + σ 2 dε 2 + σ 3 dε 3 = ρ σ dε (13) This is because a unit volume of powder (or porous) body with relative density ρ consists of the matrix material of volume ρ , thus, dW is not directly equivalent to σ dε [106].…”
Section: Constitutive Equationsmentioning
confidence: 99%
“…The powder compaction industry acknowledges that friction between the powder and tool surfaces is a key parameter that leads to inhomogeneity in engineering components made via this route. Consequently, significant effort has been expended in measuring friction and assessing its impact on compact quality [18]. Studies of this type have identified that the friction coefficient between the powder and the tool set surface is affected by a range of parameters.…”
Section: Contact Modelsmentioning
confidence: 99%